GrlR, a negative regulator in enteropathogenic E. coli, also represses the expression of LEE virulence genes independently of its interaction with its cognate partner GrlA - Lara-Ochoa, Cristina; Huerta-Saquero, Alejandro; Medrano-López, Abraham; Deng, Wanyin; Finlay, B. Brett; Martínez-Laguna, Ygnacio; Puente, José L. (Frontiers in Microbiology, 2023)
Enteropathogenic Escherichia coli (EPEC), enterohemorrhagic E. coli (EHEC) and Citrobacter rodentium (CR) belong to a group of pathogens that share the ability to form ‘‘attaching and effacing’’ (A/E) lesions on the intestinal epithelia. A pathogenicity island known as the locus of enterocyte effacement (LEE) contains the genes required for A/E lesion formation. The specific regulation of LEE genes relies on three LEE-encoded regulators: Ler activates the expression of the LEE operons by antagonizing the silencing effect mediated by the global regulator H-NS, GrlA activates ler expression and GrlR represses the expression of the LEE by interacting with GrlA. However, despite the existing knowledge of LEE regulation, the interplay between GrlR and GrlA and their independent roles in gene regulation in A/E pathogens are still not fully understood. Using different EPEC mutants, cat transcriptional fusions and protein secretion and expression assays, we showed that the transcriptional activity of LEE operons increased under LEE-repressing growth conditions in the absence of GrlR. Interestingly, GrlR overexpression exerted a strong repression effect over LEE genes in wild-type EPEC and, unexpectedly, even in the absence of H-NS, suggesting that GrlR plays an alternative repressor role. Moreover, GrlR repressed the expression of LEE promoters in a non-EPEC background. Experiments with single and double mutants showed that GrlR and H-NS negatively regulate the expression of LEE operons at two cooperative yet independent levels. In addition to the notion that GrlR acts as a repressor by inactivating GrlA through protein-protein interactions, here we showed that a DNA-binding defective GrlA mutant that still interacts with GrlR prevented GrlR-mediated repression, suggesting that GrlA has a dual role as a positive regulator by antagonizing GrlR’s alternative repressor role. In line with the importance of the GrlR-GrlA complex in modulating LEE gene expression, we showed that GrlR and GrlA are expressed and interact under both inducing and repressing conditions. Further studies will be required to determine whether the GrlR alternative repressor function depends on its interaction with DNA, RNA, or another protein. These findings provide insight into an alternative regulatory pathway that GrlR employs to function as a negative regulator of LEE genes.